Bioconcentration, behavioral, and biochemical effects of the non-steroidal anti-inflammatory drug diclofenac in Daphnia magna - Nkoom, Matthew; Lu, Guanghua; Liu, Jianchao; Dong, Huike; Yang, Haohan (Environmental science and pollution research international, 2019)
The non-steroidal anti-inflammatory drug (NSAID) diclofenac is one of the most frequently studied as well as controversially discussed pharmaceutically active drug on the subject of its relevance to the environment. This study was conducted to assess the bioconcentration potential of diclofenac and its behavioral and biochemical effects in Daphnia magna . The bioconcentration factors of diclofenac determined after 48 h of aqueous exposure in Daphnia magna were 70.94 and 8.02 for the nominal exposure concentrations of 5 and 100 μg/L, respectively. Diclofenac exposure obviously decreased the filtration and ingestion rates of the daphnids. A significant increase of the acetylcholinesterase activity that was observed in this study indicates that diclofenac might not have neurobehavioral toxicity in Daphnia magna . Significant induction of malondialdehyde content is an indication of overproduction of reactive oxygen species leading to oxidative damage in daphnids after diclofenac exposure. Moreover, significant inhibition of the superoxide dismutase, catalase, and glutathione reductase activities implies that the antioxidant defense system of Daphnia magna was overwhelmed. Also, significant inhibition of glutathione s-transferase activity might point to the fact that the enzyme was not capable to detoxify diclofenac in Daphnia magna . These findings indicate that diclofenac can accumulate and consequently stimulate behavioral and biochemical disturbances in Daphnia magna .